Yearbook of International Trade Statistics-1974, 1978,1982, 1985, Annuaire Statistique Du Commerce International - Detartment if International Economic and Social Affairs Statistical Office (New York : United Nations, 1974)
This volume comprise of the statistics for individual countries' external trade performance in terms of the overall trends in current values as well as in volume and price.
sju 24/01/2019
Ref
Keywords: Yearbook; USA